A Multifunctional Metallohydrogel with Injectability, Self‐Healing, and Multistimulus‐Responsiveness for Bioadhesives. Issue 10 (7th August 2018) - Dai, Cong; Zhou, Zhengnan; Guan, Zhenpeng; Wu, Yuxuan; Liu, Yan; He, Jiapeng; Yu, Peng; Tu, Lingjie; Zhang, Fengmiao; Chen, Dafu; Wang, Renxian; Ning, Chengyun; et al.
Abstract: Multifunctional hydrogel bioadhesives have great prospects in biomedical applications, but their design still faces great challenges, such as multiple and tedious chemical modifications. However, it is difficult to integrate injectable, self‐healing, and stimulus‐responsive properties together. A facile approach based on dynamic metal‐ligand coordination chemistry between chondroitin sulfate (CS) and Fe 3+ in the design and synthesis of novel multifunctional metallohydrogel bioadhesives is reported. This CS‐based hydrogel not only has strong tissue adhesion superior to that of commercial fibrin glue, but also exhibits an excellent self‐healing ability and injectability, which are beneficial in the field of bioadhesives. Moreover, the hydrogels undergo a rapid gel–sol transformation in response to multiple external stimuli, including pH, ions, neutral molecules, and chemical redox reactions enabling the rapid removal of the bioadhesive. In addition, metallohydrogels are rapidly formed within 10 s, quick enough to promptly seal the tissue. Importantly, the multifunctional CS‐based bioadhesives are shown to exhibit good biocompatibility, thus allowing the developed materials to meet key requirements for next‐generation tissue adhesives. Abstract : In this study, a multifunctional supramolecular hydrogel is prepared by metal‐cross‐linking Fe 3+ ions and chondroitin sulfate. In addition, the hydrogel is shown to achieve gelation in 10 s and possesses good injectability, excellent self‐healing ability, and rapid multistimulus‐responsiveness due to the large number of noncovalent bonds in the hydrogel.